The Fear Traumatization: Psychological Consequences of Covid-19 Pandemic - Ekimova V.I.; Rozenova M.I.; Litvinova A.V.; Koteneva A.V. (Современная зарубежная психология, 2021)
The COVID-19 pandemic, combined with high transmission and mortality rates of the infection, created an unprecedented state of emergency worldwide. The risk of infection and death, the experience of social isolation, alongside with loss of control over the situation and frightening information caused the "pandemic of fear" that had spread across regions and countries. The aim of this review is to summarize and to analyze the results of numerous studies of the COVID-19 pandemic psychological consequences for the population of different countries and the world as a whole, as well as for individual categories of population, and COVID-19 related risk factors. Relatively high levels of fear, anxiety, depression, post-traumatic stress disorder, psychological distress and stress have been observed and continue to be observed among the population of China, Spain, Italy, Iran, the United States, Turkey, Nepal, Denmark, and other countries. The most severe symptoms of psychological trauma are demonstrated by medical workers, women, young people, those who had lost their jobs during the crisis, people with chronic diseases, etc. It is especially important to continue international and interdisciplinary researches aimed at identifying and mitigating the dangerous effects of COVID-19 on people's mental health and psychological well-being.